Implementasi Hadhanah Pada Keluarga Pra Sejahtera (Di Kelurahan Talang Ulu Kabupaten Rejang Lebong) - Ramayani, Mira; Yusefri, Yusefri; Hartini, Hartini (Institut Agama Islam Negeri (IAIN) Curup, 2022)
The role of hadhanah is very important in a family, especially underprivileged families who are in the spotlight of researchers. However, based on facts on the ground, it shows that pre-prosperous families have not implemented hadhanah properly. Therefore, further research is needed to find out how the understanding of underprivileged families in Talang Ulu Village, Rejang Lebong Regency about hadhanah, how to implement hadhanah in underprivileged families in Talang Ulu Village, Rejang Lebong Regency. This type of research is a qualitative field research. The data sources in this study are primary data sources, secondary data sources and tertiary data sources. The data collection techniques of this research were observation, interviews and documentation. The results showed that understanding of hadhanah by pre-prosperous families was quite good, as seen from the results of the study which showed that understanding ofhadhanah is an obligation of both parents, and if it is not implemented, it includes people who sin for wasting their children, will plunge the child on things that can damage the child's religion. The implementation of hadhanah in underprivileged families in Talang Ulu Village, Rejang Lebong Regency has not been implemented properly, it can be seen that parents let their children leave the house at sunset, let their children leave the five daily prayers on purpose, and do not supervise children's interactions which results in children who pregnant out of wedlock and must marry underage. Parents and families should set an example from themselves for their children, if parents do good things it will be an example and role model for children and become a good habit for the child.